Hemolysin Co-regulated Family Proteins Hcp1 and Hcp2 Contribute to Edwardsiella ictaluri Pathogenesis - Kalindamar, Safak; Abdelhamed, Hossam; Kordon, Adef O.; Pinchuk, Lesya M.; Karsi, Attila (Frontiers in Veterinary Science, 2021)
Edwardsiella ictaluri is a Gram-negative facultative intracellular pathogen causing enteric septicemia of catfish (ESC), a devastating disease resulting in significant economic losses in the U.S. catfish industry. Bacterial secretion systems are involved in many bacteria's virulence, and Type VI Secretion System (T6SS) is a critical apparatus utilized by several pathogenic Gram-negative bacteria. E. ictaluri strain 93-146 genome has a complete T6SS operon with 16 genes, but the roles of these genes are still not explored. In this research, we aimed to understand the roles of two hemolysin co-regulated family proteins, Hcp1 (evpC) and Hcp2. To achieve this goal, single and double E. ictaluri mutants (EiΔevpC, EiΔhcp2, and EiΔevpCΔhcp2) were generated and characterized. Catfish peritoneal macrophages were able to kill EiΔhcp2 better than EiΔevpC, EiΔevpCΔhcp2, and E. ictaluri wild-type (EiWT). The attachment of EiΔhcp2 and EiΔevpCΔhcp2 to ovary cells significantly decreased compared to EiWT whereas the cell invasion rates of these mutants were the same as that of EiWT. Mutants exposed to normal catfish serum in vitro showed serum resistance. The fish challenges demonstrated that EiΔevpC and EiΔevpCΔhcp2 were attenuated completely and provided excellent protection against EiWT infection in catfish fingerlings. Interestingly, EiΔhcp2 caused higher mortality than that of EiWT in catfish fingerlings, and severe clinical signs were observed. Although fry were more susceptible to vaccination with EiΔevpC and EiΔevpCΔhcp2, their attenuation and protection were significantly higher compared to EiWT and sham groups, respectively. Taken together, our data indicated that evpC (hcp1) is involved in E. ictaluri virulence in catfish while hcp2 is involved in adhesion to epithelial cells and survival inside catfish macrophages.